Association of antibody-dependent neutrophil phagocytosis with distinct antibody glycosylation profiles following typhoid vaccination - Johnson, M; Stockdale, LK; de Haan, N; Wuhrer, M; Nouta, J; Koeleman, CAM; Clarke, J; Marinou, S; Shakya, M; Colin-Jones, R; Theiss-Nyland, K; Voysey, M; et al. (Frontiers Media, 2021)
Typhoid Vi-conjugate vaccines (Vi-TCV) have been developed to control typhoid fever in children in endemic regions. Previously, in a human challenge model of typhoid, Vi-TCV was administered prior to deliberate ingestion of Salmonella Typhi by healthy adult volunteers in the UK. Vi-specific antibody-dependent neutrophil phagocytosis (ADNP) was associated with protection against enteric fever in this model, but it is not known if ADNP is induced by vaccination of children. We measured ADNP in a cohort of Nepalese children receiving a Vi-TCV in a field study to investigate whether functional antibody responses were also present in children in an endemic setting. Furthermore, we investigated relationships between the functional antibody measures and other properties of the antibody response, including Vi-IgG and IgA titres, and Fc region glycosylation. Antibody-dependent neutrophil phagocytosis significantly increased in children aged 9 months to 15 years between the day of vaccination and 28 days following administration of Vi-TCV (D28). The magnitude of ADNP was also comparable with the levels of ADNP induced by plasma from vaccinated UK adults. Neither IgG nor IgA antibody titres significantly correlated with ADNP scores at D28; however, increased vaccine-induced ADNP was associated with decreased levels of IgG1 sialylation. These data suggest that vaccination with Vi-TCV produces functional antibody responses in children, which associate with specific glycosylation patterns of the Fc region.